MONITORING LAND COVER FIRES USING SPECTRAL INDICES AND SATELLITE DATA - AlJawwadi, Taha A.T. D.; Khalaf , Ayad A.; Qubaa, Abdalrahman R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study aimed to monitor and evaluate the impact of fires on the appearance of the land surface in open and flat agricultural areas using spectral indices and Landsat8 Operational Land Imagery (OLI) satellite images. A representative area, covering 250.34 km², was selected in Nineveh Governorate in Iraq lies between latitudes (43˚ 20′ 0̋-43˚ 32′ 30̋) N and longitude (36˚ 25′ 0̋-36˚ 11′ 0̋) E on June and July 2019 in order to determine the burned area on the land, and use the resulting spectral signature to generalize it to the rest of the study area. Data from the American Landsat satellite, GIS software, and spectral indicators for vegetation covers, such as the Normalized Difference Vegetation Index (NDVI), the Soil-Adjusted Vegetation Index (SAVI), and the Normalized Burning Ratio index (NBR), were used to extract the results. Then, the Land Surface Temperature index (LST) and the difference Normalized Burning Ratio index (dNBR) were used to measure the validity of the results and the severity of the fires, respectively. After using and performing corrective processing of the spectral indices, applying the three indices and determining the difference between them for a short period of time, it was possible to discover the areas of fires and the proportions of their effects. The NDVI results showed that the area affected by very severe degradation increased due to the fires to 39.29%, while the LST increased from 47.70 to 48.39 degree. The study concluded that the area of ​​fire spread can be determined when there is a discrepancy in the pattern of spatial data that are close in date of capture and by using spectral indices.